Arginine vasopressin injection rescues delayed oviposition in cyp19a1b-/- mutant female zebrafish - Shaw, Katherine; Lu, Chunyu; Liu, Xiaochun; Trudeau, Vance L. (Frontiers in Endocrinology, 2023)
In zebrafish, estrogens produced in the ovaries via Cyp19a1a activity are required for both sexual differentiation of the ovary during early development as well as maintenance of the ovarian state during adulthood. The importance of Cyp19a1b that is highly expressed in the brain for female reproduction is still under study. We previously reported that female cyp19a1b -/-mutant zebrafish have significantly lower brain estradiol levels and impaired spawning behavior characterized by an increased latency to oviposition during dyadic sexual behavior encounters. In the current study, we provide evidence that the delayed oviposition in female cyp19a1b -/-mutants is linked to impaired arginine vasopressin (Avp) signalling. Droplet digital PCR experiments revealed that levels of the estrogen receptors, avp, and oxytocin (oxt) are lower in the hypothalamus of mutant females compared to wildtype fish. We then used acute intraperitoneal injections of Avp and Oxt, along with mixtures of their respective receptor antagonists, to determine that Avp can uniquely rescue the delayed oviposition in female cyp19a1b -/- mutants. Using immunohistochemistry, we demonstrated that Cyp19a1b-expressing radial glial cell (RGC) fibres surround and are in contact with Avp-immunopositive neurons in the preoptic areas of the brain. This could provide the neuroanatomical proximity for RGC-derived estrogens to diffuse to and activate estrogen receptors and regulate avp expression levels. Together these findings identify a positive link between Cyp19a1b and Avp for female zebrafish sexual behavior. They also suggest that the female cyp19a1b -/-mutant behavioral phenotype is likely a consequence of impaired processing of Avp-dependent social cues important for mate identification and assessment.